Incentives and judicially determined terms of employment in India: endemic trade-off between justice and efficiency - Singh, Jaivir (2003)
This paper begins by presenting an account of some of the successive restrictions imposed by the law - both by the statutes and their interpretation by courts - that define the parameters within which Indian industrial establishments are obliged to function in relation to dismissing workers. This description of the substantive content of the law indicates that the restrictions on the termination of errant workers are embedded in judicial concerns of equality. Translated into procedure this requires, one, that penalties imposed on workers be proportional to misconduct, and two, that stringent evidentiary requirements by met in every case of worker termination. These constraints lead to a trade-off is inevitable or it is possible to ease the trade-off by structurally reorienting the law. - Reproduced.
Keywords: Employment - India; Conditions of employment - India; Conditions of employment